2005
DOI: 10.1111/j.1540-8159.2005.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Ten Year Follow‐Up After Radiofrequency Catheter Ablation for Atrioventricular Nodal Reentrant Tachycardia in the Early Days Forever Cured, or a Source for New Arrhythmias?

Abstract: KIMMAN, G.P., ET AL.: Ten Year Follow-Up After Radiofrequency Catheter Ablation for AtrioventricularNodal Reentrant Tachycardia in the Early Days. Background: Radiofrequency (RF) catheter ablation is highly effective with a low complication rate. However, lesions created by RF energy are irreversible, inhomogeneous, and therefore potentially proarrhythmic.Objectives: The aim of this study was to examine the magnitude and importance of long-term proarrhythmic effects of RF energy.Methods and Results: Between 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 16 publications
1
34
1
Order By: Relevance
“…In elderly patients, development of late AV block years after AVNRT ablation has been described. 29 Secondary arrhythmias, which might have been induced by atrial scarring after ablation, 30 were not observed among our patients. According to our findings, AVNRT ablation in pediatric patients was a safe procedure with no relevant late morbidity.…”
Section: Discussionmentioning
confidence: 87%
“…In elderly patients, development of late AV block years after AVNRT ablation has been described. 29 Secondary arrhythmias, which might have been induced by atrial scarring after ablation, 30 were not observed among our patients. According to our findings, AVNRT ablation in pediatric patients was a safe procedure with no relevant late morbidity.…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, most patients indicate an improvement in quality of life after the ablation. It is well known that palpitations after AVNRT ablation often bear no relationship with the original arrhythmia: some patient complain of sinus tachycardia, atrial premature beats, ventricular premature beats or have an associated arrhythmia [3, 15]. Moreover, after AVNRT ablation atrial flutter might become present, or ectopic atrial tachycardia may arise due to the scarring [3].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that palpitations after AVNRT ablation often bear no relationship with the original arrhythmia: some patient complain of sinus tachycardia, atrial premature beats, ventricular premature beats or have an associated arrhythmia [3, 15]. Moreover, after AVNRT ablation atrial flutter might become present, or ectopic atrial tachycardia may arise due to the scarring [3]. It also has to be said when interpreting these results that atrial or ventricular premature beats, which often initiate AVNRT, are not treated by ablation of the slow pathway and may continue to provoke symptoms in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kimman et al (18) showed new types of recurrence of SVT after successful RFA in children. Similarly, Mujovic et al (19) reported new types of arrhythmia in 16% of 124 adult patients who underwent RFA for accessory pathways.…”
Section: Discussionmentioning
confidence: 99%